1974
DOI: 10.2135/cropsci1974.0011183x001400030016x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Resistance in Maize to First‐ and Second‐Brood European Corn Borer1

Abstract: One 10‐inbred‐line diallel of maize (Zea mays L.) was evaluated for 2 years for resistance to second‐brood European corn borer [Ostrinia nubilalis (Hübner)], and a second 10‐line diallel was evaluated for 1 year for resistance to first and second broods. First‐brood evaluations were based on leaf‐feeding ratings in the pretassel stage, and second‐brood evaluations were based on plant‐cavity counts in mature plants. Variations attributed to general combining ability and general combining ability ✕ years were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…Even though B73 is known to be highly susceptible to 2ECB, the resistant allele at two of the seven putative QTLs for tunnel length was contributed by this inbred. Similar results were reported for the highly susceptible inbred 0h43 that positively contributed to resistance of the progenies in two sets of diallel crosses (Jennings et a!., 1974). Scott et a!.…”
Section: Discussionsupporting
confidence: 82%
“…Even though B73 is known to be highly susceptible to 2ECB, the resistant allele at two of the seven putative QTLs for tunnel length was contributed by this inbred. Similar results were reported for the highly susceptible inbred 0h43 that positively contributed to resistance of the progenies in two sets of diallel crosses (Jennings et a!., 1974). Scott et a!.…”
Section: Discussionsupporting
confidence: 82%
“…Very little information is available on the genetic factors controlling resistance to ear damage except that they are not correlated to those for sheath-collar resistance . Tests of combining ability indicated that general combining ability accounted for a greater percent of the total variation among crosses than specific combining ability for leaf feeding (Jennings et al ., 1974), sheath-collar damage (Kim et al ., 1989b) and stalk damage (Jenpings et al ., 1974) . There were no tests of combining ability for ear resistance reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to the first generation has been easy to find (Guthrie and Dicke, 1972) (Russell et al, 1974). Because several loci are involved (Jennings et al, 1974a) and 80-85% r.h, in total darkness. Drinking water for the moths was provided by spraying plain water on top of the cloth.…”
Section: Varietal Resistancementioning
confidence: 99%